Children with Visual Imparments in the Transition Period from Preschool to Primary School - Prudņikova, Ilga; Jankovska, Jekaterīna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
In today`s educational system, the transition from pre-school to primary school is considered as a traditional, however, the transition between education is related to a change in the child`s life. Preschool children`s readiness for school has always been a pressing problem for both: in school practice and in theory of pedagogy. This paper analyses the key theories, dealing with child development and learning processes, interaction with others and surrounding environment impacts on child development. A new perspective, which is closely related to these previously mentioned theories, is equivalent to the ecosystem approach, with is defined as a new approach with a view on children`s with visual impairments transition „pre-school – primary school” successful overcoming is needed on planned and targeted support.